Pd/Cu-Catalyzed tandem head-to-tail dimerization/cycloisomerization of terminal ynamides for the synthesis of 5-vinyloxazolones. Issue 14 (14th March 2017) - Tang, Luning; Huang, Hai; Xi, Yang; He, Guangke; Zhu, Hongjun
Abstract : This is the first Pd/Cu-catalyzed tandem head-to-tail dimerization/cycloisomerization of terminal ynamides for the synthesis of 5-vinyl-oxazolones. Abstract : An attractive and novel methodology involving Pd/Cu-catalyzed tandem head-to-tail dimerization/cycloisomerization of terminal ynamides for the synthesis of 3, 5-disubstituted oxazolones was developed. Under Pd(PPh3 )2 Cl2 /CuI cooperative catalyzed reaction conditions, it provided efficient access to 5-vinyloxazolones with exceptional functional group tolerance and good chemoselectivity. The control experiments demonstrated that Pd(PPh3 )2 Cl2 serves a key role in the dimerization of terminal ynamides and shows low catalytic activity in the intramolecular cyclization. Moreover, the hetero-Diels–Alder reaction of product 5-vinyloxazolones was also described, which provided polycyclic oxazolones in good yield.